Hubungan Umur, Pendidikan dan Pekerjaan Ibu dengan Akseptor KB Implant di Puskesmas Sri Gunung Kabupaten Musi Banyuasin Tahun 2019 - Paula Citra Hakim S; Siti Aisyah; Eka Afrika (Universitas Batanghari Jambi, 2021)
The number of acceptors for family planning implants is currently still very low due to the lack of knowledge of acceptors about the quality of family planning implants that are more effective, it is known that family planning programs have a very important role in suppressing population growth, especially prevention of maternal death and morbidity, implants are contraceptives that are inserted under skin, usually attached to the upper arm. This study aims to determine the relationship between age, education and work of mothers with family planning implant acceptors at the Srigunung Health Center, Musi Banyuasin Regency in 2019. The purpose of this study is to determine the relationship between age, education and occupation of mothers with implant family planning acceptors at Srigunung Health Center in 2019. This study using an analytic survey with a cross sectional approach. The population of this study were all women of childbearing age who were active family planning participants visiting the Srigunung Public Health Center, Musi Banyuasin District. The sample of this study were 97 respondents who were taken systematically randomly by dividing the number of samples desired by using the random sampling method. Based on the analysis, it was found that there was a significant relationship between age (ρ value 0,000), education (ρ value 0,000), maternal occupation (ρ value 0,000) with family planning acceptors at the Sri Gunung Puskesmas, Musi Banyuasin Regency in 2019. The conclusions in this study can be seen that there is a relationship between age, education and occupation of mothers with family planning implant acceptors at the Sri Gunung Puskesmas, Musi Banyuasin Regency in 2019.